2016
DOI: 10.1016/j.neuroimage.2016.07.026
|View full text |Cite
|
Sign up to set email alerts
|

Imaging of cerebral α4β2* nicotinic acetylcholine receptors with (−)-[18F]Flubatine PET: Implementation of bolus plus constant infusion and sensitivity to acetylcholine in human brain

Abstract: The positron emission tomography (PET) radioligand (−)-[18F]flubatine is specific to α4β2∗ nicotinic acetylcholine receptors (nAChRs) and has promise for future investigation of the acetylcholine system in neuropathologies such as Alzheimer's disease, schizophrenia, and substance use disorders. The two goals of this work were to develop a simplified method for α4β2∗ nAChR quantification with bolus plus constant infusion (B/I) (−)-[18F]flubatine administration, and to assess the radioligand's sensitivity to ace… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
54
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(55 citation statements)
references
References 56 publications
1
54
0
Order By: Relevance
“…The presented results should be seen in the context of previous metabolism studies on both enantiomers of flubatine and [ 18 F]flubatine [ 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 ]. In particular, the characterisation of phase I metabolites of (+)- 1 formed by HLM and MLM, as well as the assignment of corresponding incubated with radiometabolites in mouse, published by our group [ 4 ], are highly relevant for the discussion.…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…The presented results should be seen in the context of previous metabolism studies on both enantiomers of flubatine and [ 18 F]flubatine [ 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 ]. In particular, the characterisation of phase I metabolites of (+)- 1 formed by HLM and MLM, as well as the assignment of corresponding incubated with radiometabolites in mouse, published by our group [ 4 ], are highly relevant for the discussion.…”
Section: Discussionmentioning
confidence: 53%
“…Their development starting from the alkaloid (−)-epibatidine [ 1 ], originally isolated from the poison dart frog Epipedobates anthonyi , has been widely reported [ 2 , 3 , 4 ]. In the framework of preclinical and clinical studies, the metabolism of (−)-[ 18 F] 1 in pigs [ 5 ], rhesus monkeys [ 6 , 7 , 8 ], and in humans [ 3 , 9 , 10 , 11 ] was examined mainly with the purpose of determination of the fraction of unchanged tracer over time to enable a metabolite correction of the PET data obtained. In human, (−)-[ 18 F] 1 showed a high metabolic stability [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…This difference was small since only a low dose to avoid peripheral side effects. However, this finding suggested that (−)-18 F-Flubatine is probably sensitive to changes in acetylcholine levels in humans (Hillmer et al 2016a).…”
Section: (−)-18 F-flubatinementioning
confidence: 98%
“…These preclinical investigations suggest that sensitivity for measuring changes of extracellular acetylcholine could feasible with all these tracers. In keeping with this assumption, a recent study in humans demonstrated the use of bolus/infusion protocol for accurate quantification of (−)-[ 18 F]flubatine binding parameters in 120 min of physostigmine-induced changes in acetylcholine levels 94 suitable for future application in clinical studies.…”
Section: Types Of Challenges That Modulate Neurotransmission and mentioning
confidence: 98%